Decolonising pedagogy in practice: cuerpo-territorio to consolidate students´ learning - Caretta, Martina Angela; Pepa, Mariasole (Journal of geography in higher education, 2024)
Cuerpo-territorio is a method stemming from Latin American geography, which recognizes the centrality of situated and embodied experiences as a form of knowing. We engaged with this method in the classroom to understand how students through their embodied and situated experiences had absorbed a post-development geographic course content and how these notions had remained with them. Given that emotions, particularly when elicited by images play a major role in consolidating knowledge, we asked students to explore their embodied feelings related to the course content by reflecting and representing them in a visual form on a poster. Through this paper, we aim to contribute to the debate on the importance of applying decolonial strategies in the classroom by widening the methodological toolbox of our geography colleagues. We find that, given the diversity of the students' population, working with a boundary object such as the posters helped students to relate to each other via the course content. Finally, reflecting and assimilating the course content through cuerpo -territorio, we argue, was conducive to consolidating learning outcomes, while students experienced knowledge co-creation with their peers.